Effect of alumina nanoparticles on the thermal properties of carbon fibre‐reinforced composites. (20th March 2013) - Rallini, Marco; Natali, Maurizio; Monti, Marco; Kenny, José M.; Torre, Luigi
ABSTRACT In this work, we investigated the thermal behaviour of a carbon‐fibre composite impregnated with nano‐alumina‐based nanocomposites. First of all, we demonstrated that it is possible to obtain good dispersion and distribution of nanoparticles by mechanical mixing. In all the studied filler percentages, the presence of the ceramic filler did not affect the processability of the blends and the mechanical properties of the composites. First, the thermal stability of the nanocomposites was investigated by thermogravimetric analysis (TGA). Then, the fire reaction of the fibre‐reinforced composites was studied at different heat fluxes, by TGA, cone calorimeter and exposure to a direct flame. In presence of an oxidizing hyperthermal environment, the experimental data suggested the role of ceramic particles as anti‐oxidizer agent for the char and the carbon fibres. Moreover, the use of alumina nanoparticles allowed a slight reduction of heat release rate. Particularly at a heat flux of 35 kW/m2, the burnt material containing the higher quantity of nano‐alumina maintained a residual structural integrity because of the higher presence of char that bound together the fibres. To estimate the integrity of the composites after exposure to a direct flame (heat flux 500 kW/m2), mechanical tests were carried out on the burnt specimens. Copyright © 2013 John Wiley & Sons, Ltd.